Evaluation of cytotoxicity and biodistribution of mesoporous carbon nanotubes (pristine/-OH/-COOH) to HepG2 cells in vitro and healthy mice in vivo. Issue 9 (26th November 2022) - Du, Yujing; Chen, Zhipei; Hussain, M. Irfan; Yan, Ping; Zhang, Chunli; Fan, Yan; Kang, Lei; Wang, Rongfu; Zhang, Jianhua; Ren, Xiaona; Ge, Changchun
Abstract: Mesoporous carbon nanotubes (mCNTs) hold great promise interests, owing to their superior nano-platform properties for biomedicine. To fully utilize this potential, the toxicity and biodistribution of pristine and surface-modified mCNTs (-OH/-COOH) should preferentially be addressed. The results of cell viability suggested that pristine mCNTs induced cell death in a concentration-dependent manner. As evidence of reactive oxygen species (ROS), malondialdehyde (MDA) and superoxide dismutase (SOD), pristine mCNTs induced noticeable redox imbalance. 99m Tc tracing data suggested that the cellular uptake of pristine mCNTs posed a concentrate-dependent and energy-dependent manner via macropinocytotic and clathrin-dependent pathways, and the main accumulated organs were lung, liver and spleen. With OH modification, the ROS generation, MDA deposition and SOD consumption were evidently reduced compared with the pristine mCNTs at 24/48 h high-dose exposure. With COOH modification, the modified mCNTs only showed a significant difference in SOD consumption at 24/48 h exposure, but there was no significant difference in the measurement of ROS and MDA. The internalization mechanism and organ distribution of modified mCNTs were basically invariant. Together, our study provides evidence that mCNTs and the modified mCNTs all could induce oxidative damage and thereby impair cells. 99m Tc-mCNTs can effectively trace the distribution of nanotubes in vivo .